2021
DOI: 10.1049/cvi2.12012
|View full text |Cite
|
Sign up to set email alerts
|

Multi‐level feature fusion network for crowd counting

Abstract: Crowd counting has become a noteworthy vision task due to the needs of numerous practical applications, but it remains challenging. State‐of‐the‐art methods generally estimate the density map of the crowd image with the high‐level semantic features of various deep convolutional networks. However, the absence of low‐level spatial information may result in counting errors in the local details of the density map. To this end, a novel framework named Multi‐level Feature Fusion Network (MFFN) for single image crowd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 55 publications
0
7
0
Order By: Relevance
“…It was superior to existing methods. The ablation study confirmed the effectiveness of each component [7]. Shen et al built a hyper-spectral classification strategy ground on a three-dimensional MSFF strategy and channel attention mechanism to address the difficulties of traditional 2D or 3D deep CNNs in hyper-spectral image classification.…”
Section: Related Workmentioning
confidence: 72%
“…It was superior to existing methods. The ablation study confirmed the effectiveness of each component [7]. Shen et al built a hyper-spectral classification strategy ground on a three-dimensional MSFF strategy and channel attention mechanism to address the difficulties of traditional 2D or 3D deep CNNs in hyper-spectral image classification.…”
Section: Related Workmentioning
confidence: 72%
“…The second was where to place the attention mechanism in the model. There are various options for where to insert attention into the model, including introducing it in densecells ( Bastings and Filippova, 2020 ), adding it in denseblocks ( Wei et al, 2019 ; Zhou et al, 2019 ; Wang et al, 2021 ), inserting it between denseblocks and transitions ( Jia et al, 2022 ; Jia et al, 2023 ), bring in the attention mechanism in the transition layer ( Song et al, 2021 ), or attaching it before the data enters DenseNet or at the end of the model prediction.…”
Section: Methodsmentioning
confidence: 99%
“…Based on the coarse extraction of features in Section 2. H can be obtained by fusing three depth-level features from the VGG16 pillar network [16].…”
Section: Improved Unimodal Characterizationmentioning
confidence: 99%